Pathologic Characteristics, Natural History, and Prognostic Implications of BRAFV600E Mutation in Pediatric Papillary Thyroid Carcinoma. (June 2017) - Hardee, Steven; Prasad, Manju L; Hui, Pei; Dinauer, Catherine A; Morotti, Raffaella A
The BRAF V600E mutation is the most common genetic aberration in papillary thyroid cancer (PTC), found in up to 68% of PTC in adults where it is associated with aggressive features. The incidence of this mutation in pediatric PTC is less frequent, reported as 0%–20% in the past and up to 63% in one recent series. Data suggest the mutation is not associated with an aggressive course in children; however, there are limited numbers of reported case series, so the prognostic implications remain poorly understood. The aim of this retrospective study was to examine the histologic characteristics and clinical outcomes of BRAF positive pediatric PTC at a single institution. A 12-year retrospective review of all thyroidectomies performed at a tertiary medical center identified 59 pediatric cases with a surgical pathology diagnosis of PTC. Fifty patients had BRAF V600E mutation analysis data and were selected for further study. BRAF V600E mutations were present in 48% of cases (n = 24) and absent in 52% (n = 26). The molecular characteristics of the BRAF negative cases will further be evaluated in future studies. BRAF positive cases occurred in patients who were on average older than the BRAF negative patients. Classic histology PTC was present in both BRAF positive and negative cases; however, only cases with classic PTC histology were positive for the mutation. No patients died and BRAF mutation was not associated with an increased recurrence rate. Our study supports BRAF V600E is more common in children than previously thought and does not portend a more aggressive clinical course.